Peran Manajemen Keuangan Dalam Mewujudkan Efektivitas Pengelolaan Sekolah Di SMA Swasta Imelda Ritonga - Rika Syahmewah; Syahrizal Efendi Lubis (Universitas Labuhanbatu, 2025)
This study aims to analyze the role of financial management in achieving the effectiveness of school management at SMA Swasta Imelda Ritonga. Financial management is an essential aspect of educational administration as it involves planning, allocation, implementation, and supervision of school funds. The effectiveness of school management is strongly influenced by the institution’s ability to manage resources optimally, transparently, and accountably. This research employs a qualitative approach with a descriptive research design. The research subjects include the principal, treasurer, vice principal, and administrative staff involved in financial management. Data were collected through in-depth interviews, observations, and documentation studies, and were analyzed through data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The findings indicate that financial management at SMA Swasta Imelda Ritonga has been implemented through annual budget planning, priority-based fund allocation, and routine supervision. However, challenges remain in terms of budget flexibility and infrastructure development. Overall, financial management plays a significant role in supporting the effectiveness of school management and improving educational quality.